Shafi'iyyah Perspective Insurance Waqf - Imam Kamaluddin; Aria Nur Akmal (al-Afkar, Journal For Islamic Studies, 2025)
Waqf Life insurance is a method of planning waqf by making an official/legal will from ownership of assets by providing the waqf in question when there is a risk/death with the consent of the heirs. By handing over the policy as a form of waqf contract to the nazhir. In this case, people who have a unit link life insurance policy from an insurance company that has sharia products after becoming a policy and securities will have the benefits or sum insured and other benefits that will be donated. The aim of this research is to determine the position of sharia insurance waqf in Islamic law according to the Syafii school of thought. The research method used is qualitative normative-empirical for benefit with the benchmark of sharia maqashid. The results of this research show that according to the Shafi school of thought, waqf benefits for sharia life insurance are not permitted. Because the ulama in the Shafi school of thought strongly oppose waqf/cash waqf, where money will run out if used.